Exploring the emerging COVID-19 research trends and current status in the field of education: a bibliometric analysis and knowledge mapping - Turgut Karakose; Murat Demirkol (Educational Process: International Journal)
Background/purpose – The current study aims to analyze the thematic structures and trends of scientific publications that examine the relationship between the COVID-19 pandemic and education, while presenting a roadmap for future research on this topic.